CORRELATION BETWEEN MASTICATORY PERFORMANCE AND QUALITY OF LIFE OF PATIENTS USING POSTERIOR DENTAL IMPLANTS - Rahayu, Yayuk Supatmi; Dewi, Ratna Sari; Odang, Roselani; Masulili, Chaidar (International Journal of Applied Pharmaceutics, 2018)
Introduction: Masticatory performance measurement to evaluate a patient's satisfaction with dentures, including patients using posterior implant-supported single crowns, contributes to prosthetic treatment. Patient satisfaction rates can affect their quality of life (QoL). However, in Indonesia, these evaluations are rarely made. Objective: This study objective was to investigate the correlation of masticatory performance to oral health-related QoL in patients using posterior implant-supported single crowns. Methods: The study design was cross-sectional using twelve patients with posterior implant-supported single crowns. The study used sociodemographic data, a QoL questionnaire, and color-changeable chewing gum (Xylitol). AÂ Spearman correlation was used to analyze the data. No significant correlation (p>0.05) was found between masticatory performance and oral health impact profile (OHIP) score. Results: This result study was expected because of the small number of subjects in the study. It is suggested that masticatory performance can be assessed objectively with color-changeable chewing gum and subjectively with a QoL questionnaire (OHIP 49-id).